Hi, A.I. - Willinger, Isa (Germany : Rise And Shine World Sales, 2019)
Chuck picks up his new robot partner, Harmony, fresh from the factory, for a road trip through California. As it turns out, Harmony likes books and can quote the American inventor and futurist, Ray Kurzweil. Grandma Sakurai is introduced to her cute robot, Pepper. Pepper is meant to keep her company, but is quite capricious and finds the old lady’s conversation topics of little interest. While Harmony and Chuck search for love, and Pepper and Grandma kill time, pressing questions arise: How will robots and artificial intelligence change our lives? And who will be the main protagonists of the future world?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films